Community Renewable Energy in the Czech Republic: Value Proposition Perspective - Pechancová, Viera; Pavelková, Drahomíra; Saha, Petr (Frontiers in Energy Research, 2022)
The community renewable energy offers much potential for sustainable projects differing in terms of regional governance, technology, social, and economic settings. However, the energy sector often lacks a systematic approach to community energy project data, and community projects are based on diversified value proposition designs. This study introduces a new concept of value proposition canvas. Four regional case studies provide essential inputs for the novel community renewable energy value proposition canvas based on the triple bottom line concept. The argument of this study is that energy communities bring together multiple positive local impacts. Moreover, we offer a novel, structured way of looking at its value propositions in the form of triple bottom line value proposition canvas. The study results might serve for the new entrants to the low carbon energy communities and decision-making authorities in energy policy.